ANALISIS PEMBERITAAN PEMBANGUNAN SEKTOR PERIKANAN - KELAUTAN PADA HARIAN KALTIM POST PERIODE JANUARI - JUNI 2014 - Andrian Nur Pratama; Erwiantono; Juliani (Jurnal Pembangunan Perikanan dan Agribisnis, 2015)
"Kaltim Post" is a daily morning newspaper published in East Borneo. Daily Kaltim Post published premiered on May 8, 2003 with the number of prints 15,000 copies. Currently Kaltim Post newspaper circulation reached 40,000 copies. Primary data collected by census of marine fisheries development news during the period January 1 to June 30, 2014. Secondary data was collected through a review of documents related to the research objectives. The results showed that the vast volume of fisheries and marine development news for six months is 76.337,46 cmk or as much as 16.67% of the total pages in the newspaper Kaltim Post.